Effects of the surface Miller index on the resonant neutralization of hydrogen anions near Ag surfaces - Chakraborty, Himadri; Niederhausen, Thomas; Thumm, Uwe (My University, 2004)
We compare the resonant neutralization dynamics of hydrogen anions in front of plane Ag surfaces of symmetries (100) and (111) using a Crank–Nicholson wave-packet propagation method. For the Ag(100) surface, the surface state, degenerate with the valence band, rapidly decays while being populated by the ion. For Ag(111), in contrast, the population of a quasi-local Shockley surface state inside the projected L-band gap impedes the electron decay into the bulk along the direction normal to the surface. This difference in the decay pattern strongly affects the survival of 1keV ions scattered from these surfaces. Scattering off the Ag(111) surface results in about an order of magnitude higher ion-survival as a function of the exit angle with respect to the surface plane compared to that off Ag(100). Results for Ag(111) show good agreement with measurements [Guillemot and Esaulov, Phys. Rev. Lett. 82, 4552 (1999)].